2010
DOI: 10.1128/aac.01548-09
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance among Respiratory Pathogens in Spain: Latest Data and Changes over 11 Years (1996-1997 to 2006-2007)

Abstract: A nationwide multicenter susceptibility surveillance study (Susceptibility to the Antimicrobials Used in the Community in España [SAUCE] project), SAUCE-4, including 2,559 Streptococcus pneumoniae, 2,287 Streptococcus pyogenes, and 2,736 Haemophilus influenzae isolates was carried out from May 2006 to June 2007 in 34 Spanish hospitals. Then, the results from SAUCE-4 were compared to those from all three previous SAUCE studies carried out in 1996-1997, 1998-1999, and 2001-2002 to assess the temporal trends in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
58
2
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 36 publications
8
58
2
14
Order By: Relevance
“…Selective pressure from the common and not always well grounded use of macrolides in childhood leads to fast expansion of streptococcal strains with limited or absent susceptibility towards these antibiotics, which could lead to serious complications and sequels after infections caused by them (16)(17)(18)(19)(20). Confirmed data for appearance of new more virulent strains of М. сatarrhalis with obligatory production of ß-lactamase during the last years have been published even in Bulgaria (8,12).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Selective pressure from the common and not always well grounded use of macrolides in childhood leads to fast expansion of streptococcal strains with limited or absent susceptibility towards these antibiotics, which could lead to serious complications and sequels after infections caused by them (16)(17)(18)(19)(20). Confirmed data for appearance of new more virulent strains of М. сatarrhalis with obligatory production of ß-lactamase during the last years have been published even in Bulgaria (8,12).…”
Section: Discussionmentioning
confidence: 64%
“…In the year 2014 100% of all samples of outpatient cases with M. сatarrhalis and almost 90% from S. аureus, produce β-lactamase, which makes them resistant to aminopenicillins without inhibitor, and moraxellae are resistant also to all first generation cephalosporins (Figure 2c-3b). So far β-lactamase from M. catarrhalis, H. influenzae and S. aureus could be suppressed by the well-known inhibitors as sulbactam and clavulonic acid, but recently there were some reports for a broader spectrum of β-lactamase activity (5,7,16).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of antibiotics prescribed are broad-spectrum agents, and there are remarkable seasonal fluctuations reflecting an inappropriate prescribing of antibiotic for RTIs caused by viruses [9]. Consequently, resistance rates of the main respiratory pathogens remain high in Spain, although a decreasing trend has been observed in the last years [10].According to the disease-specific quality indicators for outpatient antibiotic prescribing developed by the European Surveillance Antimicrobial Consumption (ESAC) [11], both the proportion of patients prescribed antibiotics and the choice of antibiotics should be taken into account when evaluating the quality of antibiotic use in general practice.This study aimed at investigating antibiotic prescribing rates and pattern of antibiotic use in patients with RTI in Spain. We assessed adherence to national recommendations in order to evaluate the extent of inappropriate antibiotic prescribing.…”
mentioning
confidence: 99%
“…The majority of antibiotics prescribed are broad-spectrum agents, and there are remarkable seasonal fluctuations reflecting an inappropriate prescribing of antibiotic for RTIs caused by viruses [9]. Consequently, resistance rates of the main respiratory pathogens remain high in Spain, although a decreasing trend has been observed in the last years [10].…”
mentioning
confidence: 99%
“…In the study by Giufre et al (2011) the resistance rates in H.influenzae to ampicillin, chloramphenicol, ciprofloxacin, cefotaxime and imipenem were found as 10.3%, 2.6%, 0%, 0% and 2.6%, respectively. In the study by Perez-Trallero et al (2010) the authors found the resistance rates to ampicillin, cefuroxime, cefotaxime and ciprofloxacin as 13.3%, 0.1%, 0% and 0.2% respectively.…”
Section: Resultsmentioning
confidence: 99%